Gaya Kepemimpinan Dan Upaya Kepala Sekolah Dalam Implementasi Kurikulum Merdeka (IKM) Di SMP Negeri 2 Wanasaba - Mawardi, Mawardi; Mohzana, Mohzana; Nursaly, Baiq Rismarini (Educatio, 2024)
This study aims at exploring the leadership style and efforts of the school principal in the implementation of Kurikulum Merdeka at SMP Negeri 2 Wanasaba. A case study method with a qualitative approach was employed in this research. The subjects (informants) of this study consisted of 1 (one) school principal, 2 (two) teachers, 1 (one) administrative staff, and 3 (three) students. Data were collected by using three techniques those are: observation, interviews, and document analysis. The results indicate that the principal’s leadership style is transformational, as the principal consistently empowers and motivates teachers and staff. The leadership style also tends to be democratic, with the principal involving teachers and staff in designing and implementing school programs, particularly in the implementation of Kurikulum Merdeka. Furthermore, several concrete efforts have been identified that the principal has undertaken to successfully implement Kurikulum Merdeka. These efforts include involving administrative staff in meeting the needs for teaching materials, conducting workshops/training at the end of the academic year, enrolling teachers in various training programs, observing the performance of teachers and administrative staff, engaging parents in socializing the implementation of Kurikulum Merdeka, monitoring the utilization of learning communities established by educational units, and facilitating all necessary resources to support the learning process.